Study on Adhesive and Microstructure Properties of Rice Husk Ash-Based Geopolymer Hybrid Alkyd Coating - Mohd Náim Abdullah; Faizal Mustapha; Mazli Mustapha; Tabrej Khan; Tamer A Sebaey (Journal of Natural Fibers)
Ensuring strong adhesion, especially under varying environmental conditions, is a significant challenge in the field of coating technology. This research aims to enhance alkyd paint adhesive strength by incorporating rice husk ash-based geopolymer (GP-RHA) as a filler. Response Surface Methodology (RSM) technique was employed to systematically study the impact of GP-RHA levels on the adhesive strength of alkyd coatings under dry and wet conditions. The morphology of the coatings was analyzed using SEM-EDX. In dry pull-off test, the incorporation of GP-RHA in alkyd coatings led to an improvement in adhesive strength with the highest recorded adhesive strength of 3.9 MPa at a ratio of 41.67% wt. GP-RHA and 58.33% wt. alkyd paint. However, this higher proportion of GP-RHA resulted in the formation of a larger pore sizes hybrid coating, further causing water infiltration into the coating’s pore structure in wet pull-off test. Outcomes of this research showed the promising potential of GP-RHA filler in alkyd paint formulations to enhance adhesion. These findings offer valuable insights into the development of coatings utilizing agro-waste as a filler to improve its adhesive properties.